Effects of ischaemic post‐conditioning on the early and late testicular damage after experimental testis ischaemia–reperfusion. (26th November 2013) - Minutoli, L.; Irrera, N.; Squadrito, F.; Marini, H.; Nicotina, P. A.; Arena, S.; Romeo, C.; Antonuccio, P.; Altavilla, D.
Summary Ischaemic post‐conditioning (IPostC) might represent an innovative surgical approach to protect organs from ischaemia and reperfusion (I/R) injury. We investigated the molecular mechanisms underlying the contrasting effects of IPostC on the early and late damage induced by testicular I/R injury. Testis I/R was induced by occluding the right testicular vessels using a clip. Male rats were divided into the following groups: sham, I/R and I/R + IPostC. In the I/R group, the clip was removed after 60 min of ischaemia, and reperfusion was allowed for 30 min, 1 and 30 days. In the I/R + IPostC group, three cycles of 30‐sec reperfusion and 30‐sec ischaemia were performed after 60 min of ischaemia and then reperfusion followed up for 30 min, 1 and 30 days. Following 30‐min reperfusion, there was an increase in mitogen‐activated protein kinases (MAPKs) in I/R rats; after 1 day of reperfusion, interleukin‐6, tumour necrosis factor‐α and nuclear factor‐κB (NF‐κB) expression were significantly increased; IκB‐α expression reduced; and a marked damage in both testes was observed. IPostC inhibited MAPKs, cytokines and NF‐κB expression, augmented IκB‐α expression and decreased histological damage in testes subjected to I/R. After 30 days of reperfusion, I/R injury activated the apoptosis machinery, caused severe histological damage and reduced spermatogenic activity. By contrast, IPostC did not modify the apoptotic markers, the histological alterations as well as spermatogenic activity following 30 days of reperfusion. Our data demonstrate that IPostC protects the testis from the early damage induced by I/R injury, but it does not protect against the late damage.